Pyrosequencing based profiling of the bacterial community in the Chilika Lake, the largest lagoon of India - Pramanik, Arnab (Genom Data, 2015)
Brackish water lake is the most extraordinary reservoir for bacterial community with an adaptability of tolerance to saline stress. In the present study, metagenomic approach was implemented utilising 454-pyrosequencing platform to gain deeper insights into the bacterial diversity profile of the soil sediment of Chilika Lake, Odisha, India. Metagenome contained 68,150 sequences with 31,896,430 bp and 56.79% G + C content. Metagenome sequences data are now available at NCBI under the Sequence Read Archive (SRA) database with accession no. SRX753382. Bacterial community metagenome sequences were analysed by MG-RAST server representing the presence of 16,212 species belonging to 45 different phyla. The dominating phyla were Proteobacteria, Chloroflexi, Firmicutes, Acidobacteria, Actinobacteria, Bacteroidetes and Planctomycetes. The analysis of bacterial community datasets obtained from two different saline soil sediments revealed significant differences in bacterial community composition and diversity value providing better understanding of the ecosystem dynamics of Chilika Lake.